2020
DOI: 10.1126/science.abb9263
|View full text |Cite
|
Sign up to set email alerts
|

Genomic surveillance reveals multiple introductions of SARS-CoV-2 into Northern California

Abstract: The COVID-19 pandemic caused by the novel coronavirus SARS-CoV-2 has spread globally, with >52,000 cases in California as of May 4, 2020. Here we investigate the genomic epidemiology of SARS-CoV-2 in Northern California from late January to mid-March 2020, using samples from 36 patients spanning 9 counties and the Grand Princess cruise ship. Phylogenetic analyses revealed the cryptic introduction of at least 7 different SARS-CoV-2 lineages into California, including epidemic WA1 strains associated with Wash… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
280
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(301 citation statements)
references
References 38 publications
13
280
0
Order By: Relevance
“…According to our ISM analysis, this subtype is separated by a hamming distance of 3 from one of the major subtype of the outbreak in China, CCACCTGCCCACAAGGCGGG (the differences are at ISM positions 10, 11 and 12). Viral spread is suspected to be due to primary exposure of an individual from China to Washington state, designating this case as "WA1" [17,61]. "WA1" lineage is 27/44 noted to have three characteristic SNVs, namely, C17747T, A17858G, and C18060T which correspond matches with our ISM positions of 10, and 12 respectively [16-18, 61, 62].…”
Section: Temporal Dynamics Of Sars-cov-2 Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our ISM analysis, this subtype is separated by a hamming distance of 3 from one of the major subtype of the outbreak in China, CCACCTGCCCACAAGGCGGG (the differences are at ISM positions 10, 11 and 12). Viral spread is suspected to be due to primary exposure of an individual from China to Washington state, designating this case as "WA1" [17,61]. "WA1" lineage is 27/44 noted to have three characteristic SNVs, namely, C17747T, A17858G, and C18060T which correspond matches with our ISM positions of 10, and 12 respectively [16-18, 61, 62].…”
Section: Temporal Dynamics Of Sars-cov-2 Subtypesmentioning
confidence: 99%
“…Subsequently, further diversity was recognized as the virus continued to spread, and researchers developed a consensus reference sequence for SARS-CoV-2, to which other sequences may be compared [13]. Researchers have continued to publish studies of the specific variants in the context of localized outbreaks, such as the Diamond Princess cruise ship [14], as well as regional outbreaks and their international connections [12,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic epidemiology has been a useful tool to track the community transmission of SARS-CoV-2 in different geographical settings. Previous studies revealed that SARS-CoV-2 epidemics in Australia 9,10 , Belgium 11 , Denmark 12 , France 13 , Iceland 14 , Israel 15 , Netherlands 16 Spain 17 and the United States (US) 1820 , resulted from multiple independent introductions, followed by community dissemination of some viral strains that resulted in the emergence of national (or local) transmission clusters. Early phylogenetic analyses of SARS-CoV-2 complete genomes from the Brazilian states of Minas Gerais 21 , Sao Paulo 22 and Amazonas 23 , revealed multiple independent viral importations and limited local spread during the initial stage of the SARS-CoV-2 epidemic in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic sequencing can be used to rapidly and accurately identify the transmission routes of the pathogen [4,5]. This can then be used to trace the path of transmission within a population and to possibly identify the probable source, potentially leading to an improved public health response [6][7][8][9][10][11][12].…”
mentioning
confidence: 99%